Plasma Volume, Hydration and Nutritional Biomarker Concentrations Across the Menstrual Cycle (P24-052-19) - Aguree, Sixtus (Curr Dev Nutr, 2019)
OBJECTIVES: To examine changes in plasma volume, hydration, and micronutrient concentrations across the menstrual cycle among healthy women of reproductive age. METHODS: Healthy women aged 18 to 44 years were studied longitudinally across a single menstrual cycle (n = 35). Women made three visits (v1, v2, and v3) to the study center around cycle days 2, 12 and 21 (adjusted for individual cycle length) representing early follicular, late follicular and midluteal phases, respectively. At each visit, blood samples were collected before and after injection of indocyanine green (ICG). ICG in plasma was measured with a spectrophotometer within 2 hours of blood draw, to estimate plasma volume. Urine specific gravity (USG) was measured with a hand-held refractometer; urine and plasma osmolality were measured using freezing point depression osmometry. Serum ferritin was measured by ELISA; serum concentrations for 5 minerals were measured by inductively coupled plasma mass spectrometry. A mixed-effects model was used to examine changes in plasma volume and biomarker concentrations across the menstrual cycle; plasma volume and biomarker associations were tested with Spearman's correlation. RESULTS: Participants had a mean (SD) BMI of 21.6 (1.9) kg/m2. Plasma volume showed a non-significant decrease of 122 mL from v1 to v2 (P = 0.165; Table 1) and remained stable from v2 to v3 (P = 0.900). However, plasma osmolality decreased throughout the cycle from v1 to v3 (P < 0.001). Urine osmolality fell slightly from v1 to v2 (P = 0.214) followed by a significant rise from v2 to v3 (P = 0.026) but USG was constant across the cycle. From v1 to v3, serum magnesium concentration declined by 4.5% (P = 0.001); zinc had a similar decline that did not reach statistical significance (P = 0.057). Mean copper, calcium, manganese, ferritin, and hemoglobin concentrations did not change across the cycle (all P > 0.05). Adjusting for markers of inflammation (α1-acid glycoprotein and C-reactive protein) and plasma volume did not affect biomarker concentration changes. Plasma volume was not correlated with nutritional biomarkers at any timepoint (all P > 0.05, Table 2). CONCLUSIONS: Concentrations of micronutrients were not related to plasma volume. Some hydration and micronutrient biomarkers changed across the menstrual cycle, which could have implications for the timing of measurements in women of reproductive age. FUNDING SOURCES: The Pennsylvania State University. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: